Habitus Peduli Lingkungan : Analisis Kegiatan Lingkungn Berbasis Partisipatif - Prasetyo Adi Nugroho (Al Ulya: Jurnal Pendidikan Islam, 2018)
The focus of research is on the efforts of the school in shaping students' awareness regarding environmental conditions and commitment to care for the environment. The study uses qualitative design and uses data collection techniques in the form of observation, interviews, documentation, literature review and using Miles and Huberman data analysis techniques, namely, data reduction, data presentation, verification. The results of the study show that the environmental care commitment has not been indexed based on deep knowledge and awareness regarding environmental conditions. Students are limited to activities acting orderly in the school environment as well as discourse on environmental discipline. The behavior of students is shaped by habitus caring for the environment. Habitus cares about the environment which is represented in various regulations or environmental discipline and the obligation to care for plants is the only choice and strategy in carrying out various activities and interactions in the Adiwiyata school environment.